Pengujian Black Box pada Aplikasi Sistem Penunjang Keputusan Seleksi Calon Pegawai Negeri Sipil Menggunakan Teknik Equivalence Partitions - Misbah Syah Anwar Kesuma Jaya; Pandu Gumilang; Tresna Wati; Yohanes Philipus Andersen; Teti Desyani (Teknik Informatika Universitas Pamulang, 2019)
Support System for Decision on the Selection of Prospective Civil Servants is still an error when making changes to the data that has been entered, so that it can cause data can not be updated. So it needs to be tested to find problems with this software. Tests conducted on this software use the Black Box method based on Equivalence Partition as a whole with regard to the use, benefits, and results found from the use of the software. Equivalence Partition-based Black Box method tests the quality of the application that will be carried out by software testing documentation with the discovery of errors in each form that is divided into three error models, including errors in Functions, Data Structures and Interfaces. This test provides results where we will find out whether the software This has an error or not, and this test can guarantee the quality of this software.